A Case Report on Prednisolone Induced Pedal Edema - Ramana, P. Venkata; Susmitha, S.; Khan, Danish Ahmad; Eshma, S K; Yaseen, S M D (Indian Journal of Pharmacy Practice)
Prednisolone is a 1, 2-dehydrocortisolwhich is highly potent synthetic glucocorticosteroid which has minimal mineralocorticoid activity. Prednisolone is used as antinflammatory or immunosuppressive agent, which indicated in the treatment of various conditions, including congenital adrenal hyperplasia, psoriatic arthritis, systemic lupus erythematous, bullous dermatitis herpetiformis, seasonal or perennial allergic rhinitis. Majorly it causes Cushing Syndrome, peptic ulceration, edema, hypokalemia, muscle weakness, behavioral changes. A 55 year old female patient was consulted in the dermatology department with chief complaints of swelling and redness of blisters on mouth and fore head, difficulty while swallowing since 2 months, past medical history of patient includes, she was already taking treatment for this condition which includes Tab. Chlophenaramine malate 4mg, Tab. Prednisolone 25 mg, Tab. Vitamin C 500 mg, Oint. Clobestalol 0.05% w/v, Glycerin lotion 5ml. After 15 days, patient had complaints of swelling of both lower limbs after administration of Tab. Prednisolone, this is the reason for hospital admission. Better vigilance is necessary for implementation of safe and effective treatment for each individual patient. In-order to prevent serious adverse drug reactions of this drug, close monitoring during treatment course, creating awareness, recognition of the problem and careful management of all patients who receive this medication are essential, because use of corticosteroids causes toxic effects like abdominal tenderness, fluid retention, insomnia, muscle weakness etc. and if close monitoring is not provided during treatment course, it can cause permanent disability, morbidity, mortality.
Keywords: Prednisolone; Pedal edema; Adverse drug reaction; Blisters.